SOCIODEMOGRAPHIC FACTOR RELATIONSHIP WITH INFANT SURVIVAL IN INDONESIA - Yasmine Nurfirdaus; Philip Etabee Macdonald Bassey (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
Child  survival  can  be reflected  in  the  presence  of  the Infant Mortality Rate (IMR). Indonesia has an Infant Mortality  Rate  (IMR)  according to the 2017 IDHS, which reaches 24 deaths per 1000 live births. This figure has decreased compared to a survey conducted by the 2012 IDHS, where infant mortality reached 32 deaths per 1000 live births. Even though it experienced a decrease, the IMR in  Indonesia was higher when compared to the IMR in other Southeast Asian countries. Socioeconomic factors for individuals, families, and communities, including  the  influence  of  infant mortality. Not only that, but infant mortality can also be due to the absence of awareness  of  maternal  health. Thus,  this  study  aims to determine several  variables related to survival in infants in Indonesia. This type of research is a non-reactive study. This study uses quantitative analysis and a methodical approach with a cross-sectional approach that takes data from the 2017 IDHS. This study took a sample following the 2017 IDHS with the criteria  that mothers  who  had  babies  still  drank  breast  milk,  were  born  single,  and  were still alive after the first  three days in Indonesia. The number of respondents in this study was 7,599 mothers with babies. Analysis  of  the  research  data  using  Chi-Square  analysis.  Bivariable  analysis shows that  infants' survival  has  a  relationship  with  the mother's education, type of area, and  welfare level. However, infant survival  also  has  no  association  with  the  age of  the  mother  and birth attendants. Counseling pregnant women regarding risks, causes,